Interferências do lançamento de foguetes na qualidade de dados GNSS processados por PPP - (:unkn) unknown (Universidade Federal do Pampa, 2018)
The use of GNSS have become a part of the daily life for the humans, this tool is only possible due to a global technological structure. The gathering of these positioning data can suffer interference along the way from its transmitter on space to the receiver on land. Interferences on the GNSS wave propagation happens on the atmosphere, and during the rocket launches these interferences are more significant. The rocket launches is becoming a normal phenomenon in some parts of the Earth. This thesis has the go to determine the interferences on the quality of GNSS data processed by PPP, caused by the Falcon Heavy launch on 06/02/2018, verifying interferences that caused differences on the position absolute precision as big as ~0,46m.
Keywords: Falcon; Distúrbios ionosféricos; Posicionamento; Ionospheric disturbances; Positioning; CNPQ::ENGENHARIAS